Comparison between mini tractor trailer with grabber and tractor assisted in field FFB Collection at Ladang Ketengah Perwira Cenneh Terengganu : a case study / Mohd Hanapi Jasni - Jasni, Mohd Hanapi (Faculty of Plantation and Agrotechnology, 2016)
Mini tractor with grabber (L28000) and tractor (M9000) used in field FFB collection. This mechanization helps to increase labour productivity for in field FFB collection in the oil palm plantation. Case study was conducted to test the comparison of total cost per month for both mechanizations. Based on data collected, the total cost per month for mini tractor with grabber results is Rm 6, 877.19 cost per month and Rm 6052.9l cost per month for tractor assisted in FFB collection. The factor that affects the total cost for both mechanizations is the type of soil, topography, handling of workers and cost in implementation on tractor such as grabber and trailer. The result shows that mini tractor with grabber higher in total cost per month than tractor assisted in field FFB collection transportation